2018
DOI: 10.1371/journal.pone.0196651
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the binding behavior of flavonoids to the cyclin dependent kinase 6/cyclin D complex

Abstract: Flavonoids, a class of natural compounds with variable phenolic structures, have been found to possess anti-cancer activities by modulating different enzymes and receptors like CDK6. To understand the binding behavior of flavonoids that inhibit the active CDK6, molecular dynamics (MD) simulations were performed on six inhibitors, chrysin (M01), fisetin (M03), galangin (M04), genistein (M05), quercetin (M06) and kaempferol (M07), complexed with CDK6/cyclin D. For all six flavonoids, the 3’-OH and 4’-OH of B-rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…These results suggest that the A. hierochuntica treatment may suppress the cell cycle progression, by down-regulating the expression of Cyclin D1 and E and induce apoptosis through p53 and p21. This could be due to the rich source of phenols and flavonoids, widely reported to be cyclin inhibitors ( Mocanu et al, 2015 , Zhang et al, 2018 ), and recently identified in the methanolic leaf extracts of A. hierochuntica ( Saranya et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the A. hierochuntica treatment may suppress the cell cycle progression, by down-regulating the expression of Cyclin D1 and E and induce apoptosis through p53 and p21. This could be due to the rich source of phenols and flavonoids, widely reported to be cyclin inhibitors ( Mocanu et al, 2015 , Zhang et al, 2018 ), and recently identified in the methanolic leaf extracts of A. hierochuntica ( Saranya et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This approach based on the molecular mechanics Poisson–Boltzmann surface area (MM/PBSA) and is a common method for calculating the binding free energy between target and ligand. The calculation of the free energy always follows the same formula [ 81 ] and the corresponding equations have already been presented in numerous publications [ 82 , 83 , 84 ]. The temperature was adjusted to 298.15 K according to the MD simulation parameters.…”
Section: Methodsmentioning
confidence: 99%
“…The hydrogen-bonding force and van der Waals interactions with residues Ile19, Val27, Ala41, Glu61, Phe98, Gln103, Aap163, and Leu152 contributed to the binding affinity. These binding features of flavonoid inhibitors may provide valuable insight into the development of CDK6 inhibitors as chemopreventive agents [ 39 ].…”
Section: Cmda Of Catechin-protein Interactionmentioning
confidence: 99%